HLA-G and the MHC Cusp Theory - Scavuzzi, Bruna Miglioranza; van Drongelen, Vincent; Holoshitz, Joseph (Frontiers in Immunology, 2022)
Human leukocyte antigens (HLA) are significant genetic risk factors in a long list of diseases. However, the mechanisms underlying these associations remain elusive in many cases. The best-characterized function of classical major histocompatibility complex (MHC) antigens is to allow safe presentation of antigenic peptides via a self/non-self-discrimination process known as ‘MHC restriction’. Therefore, most hypotheses to date have posited that the observed associations between certain HLA molecules and human diseases involve aberrant antigen presentation (AP). However, these hypotheses have not been experimentally validated in most human diseases, and they often represent inconsistencies with current knowledge. To offer answers to the inconsistencies, a decade ago we have invoked the MHC Cusp theory, postulating that in addition to its main role in AP, the MHC codes for allele-specific ligands in a conformationally-conserved cusp-like fold, which upon interaction with cognate receptors can trigger MHC-associated diseases. In the ensuing years, we have provided empirical evidence that substantiates the theory in several HLA-Class II-associated autoimmune diseases. Notably, in a recent study we have demonstrated that HLA-DRB1 alleles known to protect against several autoimmune diseases encode a protective epitope at the cusp region, which activates anti-inflammatory signaling leading to transcriptional and functional modulatory effects. Relevant to the topic of this session, cusp ligands demonstrate several intriguing similarities to the functional effects of HLA-G. The overall goal of this review is to delineate the parallels and distinctive features of the MHC Cusp theory with structural and functional aspects of HLA-G molecules.